1521 Paediatric Narcolepsy: A Video Series. (October 2012) - Gandhi, DK; Agrawal, S; Notghi, L; Wassmer, E
Abstract : Introduction: Narcolepsy often begins in childhood (30% of cases) but is infrequently recognized early in the course; only around 4% are diagnosed before age 15. There have been many reports linking H1N1 and narcolepsy. We present a video series of 4 patients that highlight the diagnostic dilemma in paediatric cases as well as association with H1N1 flu. Case Reports: 4 children (5–11 years) were referred to the Neurologists for excessive daytime sleepiness. Disturbed sleep and cataplexy developed soon after. Immunosuppressive therapy was attempted with no response in one child with rapid progression. Cataplexy initially was focal or partial and progressed to the classical description. The Multiple Sleep Latency Test (MSLT) was grossly abnormal in all them. Hypocretin was absent in the one child investigated. Autoimmune screen was negative in all. One child was treated for H1N1 and 2 had the H1N1 vaccine prior to onset of symptoms. Conclusion: The key to early diagnosis and treatment is recognition of the condition. The videos highlight the facial features and other symptoms that are clues to narcolepsy (Pentad of narcolepsy). Rapid progression is possible related to H1N1 exposure.